Development of phytosterol-loaded silver nanoparticles for ameliorating haemorrhoidal complications via the AMPK pathway—a mechanistic approach - Dubey T.; Bhanukiran K.; Hemalatha S. (My University, 2025)
The aim of the current study was to synthesize silver nanoparticles (PLSNPs) using green technology by means of phytosterol-enriched fractions from Blumea lacera extracts (EAF) and evaluate their toxicological and anti-haemorrhoidal potential. The average size of the synthesized particles was found to be 85.64 nm by scanning electron microscopy and transmission electron microscopy. Energy dispersive spectroscopy showed the elemental composition of PLSNPs to be 12.59% carbon and 87.41% silver, indicating the capping of phytochemicals on the PLSNPs. The PLSNPs were also standardized for total phytosterol content using chemical methods and high-perfromance liquid chromatography. The PLSNPs were found to be safe up to 1000 mg kg−1 as no toxicity was observed in the acute and sub-acute toxicity studies performed as per OECD guidelines. After the induction of haemorrhoids, experimental animals were treated with different doses of EAF, PLSNPs and a standard drug (Pilex) for 7 d, and on the eighth day the ameliorative potential was assessed by evaluating the haemorrhoidal (inflammatory severity index, recto-anal coefficient) and biochemical (tumour necrosis factor-alpha and interleukin-6) parameters and histology of the recto-anal tissue. The results showed that treatment with PLSNPs and Pilex significantly (p < 0.05) reduced haemorrhoidal and biochemical parameters. This was further supported by restoration of altered antioxidant status. Further, a marked reduction in the inflammatory zones along with minimal dilated blood vessels was observed in the histopathological study. The results of molecular docking studies also confirmed the amelioration of haemorrhoids via AMP-activated protein kinase (AMPK)-mediated reduction of inflammation and endothelin B receptor modification by PLSNPs. In conclusion, PLSNPs could be a good alternative for the management of haemorrhoids. © 2024 IOP Publishing Ltd.